2015
DOI: 10.1007/978-3-319-16238-6_8
|View full text |Cite
|
Sign up to set email alerts
|

On Bayesian Based Adaptive Confidence Sets for Linear Functionals

Abstract: We consider the problem of constructing Bayesian based confidence sets for linear functionals in the inverse Gaussian white noise model. We work with a scale of Gaussian priors indexed by a regularity hyper-parameter and apply the data-driven (slightly modified) marginal likelihood empirical Bayes method for the choice of this hyper-parameter. We show by theory and simulations that the credible sets constructed by this method have sub-optimal behaviour in general. However, by assuming "self-similarity" the cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The existing literature mostly focus on functionals where efficient estimation with √ n-rate is available ( [41,7,8,9]). The more general inefficient estimation with slower than root-n rate (e.g., evaluation functional) is only treated recently by [49] in Gaussian white noise model. As will be seen, our theory treat efficient and inefficient estimation in a unified framework.…”
Section: Linear Functionals On the Regression Functionmentioning
confidence: 99%
“…The existing literature mostly focus on functionals where efficient estimation with √ n-rate is available ( [41,7,8,9]). The more general inefficient estimation with slower than root-n rate (e.g., evaluation functional) is only treated recently by [49] in Gaussian white noise model. As will be seen, our theory treat efficient and inefficient estimation in a unified framework.…”
Section: Linear Functionals On the Regression Functionmentioning
confidence: 99%
“…We have encountered similar phenomena when deriving contraction rates and credible intervals for (not necessarily continuous) linear functionals of the parameter; see [13]. Since point evaluations are linear functionals, such credible intervals can be glued together into L ∞ -credible bands, where due to the Gaussianity one would expect at most a logarithmic factor to be necessary to pass from pointwise to simultaneous intervals.…”
mentioning
confidence: 89%
“…The likelihood-based empirical Bayes method seems to "estimate" the Sobolev regularity of the truth. In [13] we have shown that coverage can be retained by subtracting 1/2 from the estimate, thus under-smoothing the empirical Bayes posterior distribution. In forthcoming work with Sniekers, we note that the ordinary empirical Bayes procedure may still give good coverage for many true parameters, the loss of 1/2 being really a worst case comparison of the two norms and coverage being connected to more subtle properties of the true parameter.…”
mentioning
confidence: 99%